Does active hepatitis C virus infection increase the risk for infection due to Staphylococcus aureus? - Kaka, A. S.; Filice, G. A.; Kuskowski, M.; Musher, D. M. (European journal of clinical microbiology & infectious diseases, 2017)
Infections with Staphylococcus aureus may be more frequent in subjects with active hepatitis C virus (HCV) infection. In this retrospective dual-cohort study, we sought to determine whether persons with active HCV infection (positive HCV antibody, detectable blood HCV RNA) were at greater risk of S. aureus infection than those with spontaneously resolved HCV infection (positive HCV antibody, negative blood HCV RNA). Based on prestudy power calculation, we included 231 subjects with active HCV and 116 subjects with resolved HCV infection. The two groups were well matched at baseline, except that subjects with active HCV had a higher mean Charlson’s comorbidity index (2.2 vs. 1.3; p < 0.0001). Cohorts were followed for a mean of 3.67 years. Thirty-one of the 231 (13%) subjects with active HCV infection developed ≥1 S. aureus infection(s) as compared to 4/116 (3.4%) subjects with resolved HCV ( p = 0.004), with a trend towards more recurrent S. aureus infections in subjects with active HCV infection. The S. aureus infections were mostly serious, necessitating hospitalization and intravenous antibiotics. In the logistic regression, factors that independently predicted S. aureus infection were active HCV and Charlson’s comorbidity index. Our regression models confirmed that the enhanced susceptibility to S. aureus infections was related to active HCV infection and not attributable solely to the increased number of comorbidities [adjusted odds ratio (OR) = 3.3, 95% confidence interval (CI) 1.1–9.8; p = 0.03]. This study shows that subjects with active HCV infection have a significantly higher incidence of serious S. aureus infections than those with spontaneously resolved HCV, even after adjustment for comorbidities.